Gender Equity in Junior and Senior Secondary Education in Sub-Saharan Africa - Sutherland-Addy, Esi (Washington, DC : World Bank, 2012)
This thematic study is about gender equity in junior and senior secondary education in Sub-Saharan Africa (SSA). It consists of case studies of Ghana, Malawi, and Uganda, as well as, a review of studies undertaken over the past ten years on education in Africa with particular attention to girls' and secondary education. Gender equity at the primary level has been the focus of considerable attention within the education for all frameworks of action, but much less so at the secondary level. Evidence of gender inequity and inequality in terms of access, retention and performance in secondary education in SSA raises many questions. While transition rates from primary to secondary are higher for girls than boys, and the repetition rates are lower, girls still significantly trail behind boys in terms of secondary gross enrollment rate (GER). The purpose of this study is to document and analyze the extent and nature of gender disadvantage in junior and senior secondary education, to analyze the causes of this disadvantage and to identify strategies that may be effective in reducing or eliminating it. This thematic study will make a timely and useful contribution to the debate on Secondary Education and Training in Africa (SEIA) issues.